The Middle East : a cultural psychology - Gregg, Gary S. (Series in culture, cognition, and behavior., 2005)
For over a decade the Middle East has monopolized news headlines in the West. Journalists and commentators regularly speculate that the region's turmoil may stem from the psychological momentum of its cultural traditions or of a "tribal" or "fatalistic" mentality. Yet few studies of the region's cultural psychology have provided a critical synthesis of psychological research on Middle Eastern societies. Drawing on autobiographies, literary works, ethnographic accounts, and life-history interviews, The Middle East: A Cultural Psychology offers the first comprehensive summary of psychological writings on the region, reviewing works by psychologists, anthropologists, and sociologists that have been written in English, Arabic, and French. Rejecting stereotypical descriptions of the "Arab mind" or "Muslim mentality," Gary Gregg adopts a life-span-development framework, examining influences on development in infancy, early childhood, late childhood, and adolescence, as well as on identity formation in early and mature adulthood. He views patterns of development in the context of recent work in cultural psychology, and compares Middle Eastern patterns less with Western middle-class norms than with those described for the region's neighbors: Hindu India, sub-Saharan Africa, and the Mediterranean shore of Europe. The research presented in this volume overwhelmingly suggests that the region's strife stems much less from a stubborn adherence to tradition and resistance to modernity than from widespread frustration with broken promises of modernization-with the slow and halting pace of economic progress and democratization. A sophisticated account of the Middle East's cultural psychology, The Middle East provides students, researchers, policy makers, and all those interested in the culture and psychology of the region with invaluable insight into the lives, families, and social relationships of Middle Easterners as they struggle to reconcile the lure of Westernized lifestyles with traditional values. Book jacket